2005
DOI: 10.1038/sj.ijir.3901318
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of sildenafil as the first-step therapeutic tool for Japanese patients with erectile dysfunction

Abstract: patients were prescribed five tablets of sildenafil (50 mg) as the first step in the therapeutic management of ED. Of the 281 patients, 206 were evaluable patients. The overall success rate in achieving sexual intercourse in subjects after taking sildenafil was 77.2% (159/206), while 22.8% (47/206) were unsuccessful. The success rates in men with functional ED and organic ED were 91.4% (85/93) and 65.5% (74/113), respectively (Po0.0001). Overall, transient adverse effects of sildenafil occurred in 16 (8%) male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…As far as we know, there has been no previous report on the association between responsiveness to PDE5 inhibitor and MS. Our results show a lower response rate for sildenafil in patients with MS, which was 40%, while previous Japanese reports showed that it was about 70% in general patients [24,25]. Moreover, we revealed that the response rate significantly decreased as the number of MS components increased.…”
Section: Discussioncontrasting
confidence: 61%
“…As far as we know, there has been no previous report on the association between responsiveness to PDE5 inhibitor and MS. Our results show a lower response rate for sildenafil in patients with MS, which was 40%, while previous Japanese reports showed that it was about 70% in general patients [24,25]. Moreover, we revealed that the response rate significantly decreased as the number of MS components increased.…”
Section: Discussioncontrasting
confidence: 61%
“…10 ED is more prevalent in Japanese men than in American men. However, most elderly men do not complain about dissatisfaction despite declining sexual function.…”
Section: Discussionmentioning
confidence: 95%
“…In Japan, three PDE5‐I, sildenafil, vardenafil and tadalafil, have been approved and used clinically in recent years. Efficacy among these three drugs as assessed by specific questionnaires, such as the IIEF and the SEP has been reported to be similar in Japanese patients with ED . Although the IIEF has contributed to research and clinical practice in the area of ED including the assessment of PDE5‐I, the questionnaire provides limited assessment of erection quality beyond the ability to achieve or maintain an erection sufficient for penetration.…”
Section: Introductionmentioning
confidence: 99%
“…Efficacy among these three drugs as assessed by specific questionnaires, such as the IIEF 2 and the SEP has been reported to be similar in Japanese patients with ED. [3][4][5] Although the IIEF has contributed to research and clinical practice in the area of ED including the assessment of PDE5-I, the questionnaire provides limited assessment of erection quality beyond the ability to achieve or maintain an erection sufficient for penetration. The SEP also focuses on the success rate of penetration and maintenance of erection.…”
Section: Introductionmentioning
confidence: 99%